ANALISIS PERAN DIGITALISASI TERHADAP PENINGKATAN PENDAPATAN DAN PENYERAPAN TENAGA KERJA USAHA MIKRO, KECIL DAN MENENGAH SEKTOR JASA - Dio Kharisma Sunhadi (CURVE: Journal of Economic, Business and Accounting, 2025)
This study aims to understand the role of digitalization in the marketing of service sector MSMEs, as well as to assess its impact on increasing income, and to explore the role of these MSMEs in employment absorption in the Sidokare subdistrict. The method used is qualitative with a case study approach, involving five types of businesses such as laundry, shoe cleaning, helmet cleaning, haircuts, and bag cleaning located in the Sidokare area, Sidoarjo Regency. Data was collected through interviews, field observations, and documentation.  The results of this study show that digitalization plays an important role in increasing the competitiveness and growth of SMEs in the service sector. The use of digital platforms such as WhatsApp Business, Instagram, and Facebook is very effective in promoting online services. The positive impact of digitalization is seen in the annual increase in SME revenues. Employment absorption by SMEs in Sidokare Village also contributes positively to the local economy by creating new jobs. The responsiveness of SMEs to market demand is reflected in adjustments to the number of employees.  This study provides suggestions or recommendations emphasizing the importance of training SME employees in the use of digital technology to enhance the effectiveness of online promotion and their digital skills, which will support overall business growth.